Food and agricultural wastes-derived biochars in combination with mineral fertilizer as sustainable soil amendments to enhance soil microbiological activity, nutrient cycling and crop production - Mustafa, Adnan; Brtnicky, Martin; Hammerschmiedt, Tereza; Kucerik, Jiri; Kintl, Antonin; Chorazy, Tomas; Naveed, Muhammad; Skarpa, Petr; Baltazar, Tivadar; Malicek, Ondrej; Holatko, Jiri (Frontiers in Plant Science, 2022)
The ever-increasing human population associated with high rate of waste generation may pose serious threats to soil ecosystem. Nevertheless, conversion of agricultural and food wastes to biochar and its application either alone or with fertilizers has been shown as a beneficial approach in sustainable soil management. The present study aimed to compare the effects of agricultural (AB) and food waste derived (FWB) biochars with and without mineral fertilizer (MF) on crop growth and soil health indicators in a pot experiment. The above- and below-ground plant mass, chlorophyll fluorescence, soil enzymes and soil basal as well as substrate induced respirations were measured after amendments application to the test soil. The results showed that compared to the control, the amendment with AB enriched with MF enhanced the crop growth as revealed by higher above and below ground biomass accumulation. Moreover, both the biochars influenced soil chemical properties (pH and electric conductivity) with and without MF as compared to control. However, the amendment of soil with MF alone was most influential strategy to improve soil basal and arginin-induced respiration as well as most of the soil extracellular enzymes, those related to C, N and P cycling. Use of FWB resulted in enhanced urease activity. This suggested the role of MF and FWB in nutrient cycling and plant nutrition.